Basic Spanish-Esperanto / Esperanto-Spanish Dictionary - Leoni de León, Jorge Antonio (2018)
The first electronic dictionary published in Costa Rica was the Spanish-Esperanto / Esperanto-Spanish Glossary, which consisted of about 500 entries in each way. It was uploaded to the Cariari server of the University of Costa Rica, around September 1997. Its history and update are presented in this article. The original version lacked, among other things, grammatical marks and diacritical accents. This was corrected for this academic proposal, renamed “Spanish-Esperanto / Esperanto-Spanish Elemental Dictionary”.